Review of the degeerella species group of the genus Nemophora Hoffmannsegg, 1798 (Lepidoptera: Adelidae) from China - Sun, Hao; Wang, Shuxia; Li, Houhun (Zootaxa, 2022)
Twenty-five species of the degeerella species group in the genus Nemophora Hoffmannsegg, 1798 are reviewed from China. Fourteen species are described as new: N. spinatibaltea Sun, Wang et Li, sp. nov., N. parvaprocessa Sun, Wang et Li, sp. nov., N. bifurcifascia Sun, Wang et Li, sp. nov., N. biprocessa Sun, Wang et Li, sp. nov., N. ravidifera Sun, Wang et Li, sp. nov., N. triuga Sun, Wang et Li, sp. nov., N. seorsifascia Sun, Wang et Li, sp. nov., N. borealis Sun, Wang et Li, sp. nov., N. recurvatifera Sun, Wang et Li, sp. nov., N. digitivalva Sun, Wang et Li, sp. nov., N. apiciprocessa Sun, Wang et Li, sp. nov., N. purpuratifera Sun, Wang et Li, sp. nov., N. latirectangula Sun, Wang et Li, sp. nov. and N. gaoligongshana Sun, Wang et Li, sp. nov. Three species, N. chalybeella (Bremer, 1864), N. japonica Stringer, 1930 and N. karafutonis (Matsumura, 1932), are recorded for the first time in China. Images of adults and genitalia of all the species with available specimens in China are given, along with a key to these species. A list of all the species of the degeerella species group in the world is provided.